Ayurvedic Management of Anidra W. S. R. to Insomnia – A Review - Jain, Mahendra Kumar; Sharma, Monika (International Research Journal of Ayurveda & Yoga, 2024)
Introduction: Mansik dosha tama and Sharirik dosha Kapha are the causes of nidra. Consequently, Anidra results from any because that lowers the body’s levels of Tama and Kapha guna. Vata-pitta vridhi is stated by Acharya Vagbhatta and Sushruta in Nidranasha in Ayurveda. Anidra is regarded as one of the Vatavyadhi Nanatmaja. The Trayopasthamba are defined as Ahara (meal), Nidra (sleep), and Bramhacharya (three supporting pillars). From now on, getting enough sleep is crucial for maintaining good health. Acharya Charaka has correctly said that appropriate and improper sleep determines happiness and misery, proper and improper growth, good strength and weakness, potency and sterility, wisdom and ignorance, and life and death for a person. Anidra is compared to insomnia in contemporary science. Modern medical professionals now recommend a variety of tranquillizers to treat sleeplessness. Materials and Methods: The Brihattrayi and its commentaries, the Laghutrayi, as well as other Ayurvedic and contemporary texts, provided information on Anidra (Insomnia). Results: Ayurvedic classics including Madhura-Snigdha Anna, Gramya-Audaka-Anupa Rasa, Shali-Godhuma Pishtanna, Dadhi, Ksheera, Madhya, and Sneha all discuss how to handle sleeplessness. Insomnia might also benefit from panchakarma treatments like Nasya, Utsadana, Shirodhara, Abhyanga, Udavartana, and Samvahana. Conclusion: These medications provide significant relief during the first few days of treatment, but long-term use and continuing use have negative side effects. Thus, an attempt is made to view Anidra’s Ayurvedic management.